2015
DOI: 10.1016/j.cmi.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bloodstream infections due to colistin-resistant KPC-producing Klebsiella pneumoniae: results from a multicenter case–control–control study

Abstract: The increasing prevalence of colistin resistance (ColR) Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (Kp) is a matter of concern because of its unfavourable impact on mortality of KPC-Kp bloodstream infections (BSI) and the shortage of alternative therapeutic options. A matched case-control-control analysis was conducted. The primary study end point was to assess risk factors for ColR KPC-Kp BSI. The secondary end point was to describe mortality and clinical characteristics of these infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
112
6
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 28 publications
11
112
6
8
Order By: Relevance
“…55 The association between colonization and subsequent infection has been reported for many MDR bacteria, such as VRE, ESBL-producing Enterobacteriaceae, P. aeruginosa, S. maltophilia and carbapenem or colistin resistant K. pneumoniae. 115,116 Therefore, decolonization before the onset of neutropenia seems appealing in case of carbapenem-resistant bacteria, but very few data on the efficacy of this approach exist in this setting. For this purpose, oral gentamycin or a combination of oral gentamycin and colistin were used, with eradication rate of 40-50%, which was higher than the spontaneous eradication rate, but tended to decrease after few weeks.…”
Section: Othersmentioning
confidence: 99%
“…55 The association between colonization and subsequent infection has been reported for many MDR bacteria, such as VRE, ESBL-producing Enterobacteriaceae, P. aeruginosa, S. maltophilia and carbapenem or colistin resistant K. pneumoniae. 115,116 Therefore, decolonization before the onset of neutropenia seems appealing in case of carbapenem-resistant bacteria, but very few data on the efficacy of this approach exist in this setting. For this purpose, oral gentamycin or a combination of oral gentamycin and colistin were used, with eradication rate of 40-50%, which was higher than the spontaneous eradication rate, but tended to decrease after few weeks.…”
Section: Othersmentioning
confidence: 99%
“…108 A very recent multicenter study from the same country reported that during a 4.5 y period, the colistin resistance increased >3-fold in participating centers and related with a mortality rate of 51%. 109 Pseudomonas aeruginosa In Europe, P. aeruginosa strains with high resistance rates to aminoglycosides, ceftazidime, quinolones, piperacillin-tazobactam and carbapenems are usually reported from Southern and Eastern part of the continent. 9 However, ECDC reported that a trend analysis for 2009 to 2012 indicated a stable resistance pattern for these antimicrobials.…”
Section: Klebsiella Pneumoniaementioning
confidence: 99%
“…The other study of 13 Italian hematological units reported a rate of CRKP that increased significantly from 21.4% in 2010 to 75.9% in 2013 [6]. Neutropenia, HM and chemotherapy/radiation therapy have been recognized as independent risk factors of CRKP infection [7][8][9].…”
Section: Discussionmentioning
confidence: 99%